A STUDY ON INVESTMENT PERCEPTION BY MEN AND WOMEN ABOUT DIFFERENT INVESTMENT AVENUES WITH SPECIAL REFERENCE TO WESTERN REGION OF MUMBAI - Yadav, Madhuridevi S.; Sadvelkar, Deepti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Investment avenues are the topics where different perception is seen by men and women. The basic investment objectives are to save the money and make future stable. But when it comes to men and women the objectives are differ on the basis on short term goals and long-term goals. Investors invest in different investment avenues to fulfil their requirement and their desires in the future. And for that purpose, they invest according to their purpose.